Candi Sipamutung sebagai Simbol Budaya Batak Angkola - Harahap, Parlaungan; Wirman (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Candi Sipamutung is an archealogical site lacated in padang lawas, North Sumatra, with significant historical value, particularly within the context of the Batak Angkola community. This temple is not merely seen as a relic of the past, but also as a cultural symbol that reflects the identity and ancestral values of the local people. This study aims to reveal the symbolic meaning of candi sipamutung in Batak Angkola culture using a Phenomenological approach. The research empoloys a qualitative method with data collected through in-depth interviews with traditional leaders, cultural experets, and local residents around the temple site. The phenomenological approach is used to understand how people’s experiences and perceptions shape the meaning of the site. The findings indicate that the local community interprets Candi Sipamutung as part of their spiritual and historical heritage, lingking them to their origins and cultural identity. Although the temple is archeologically rooted in Hindu-Buddhist civilization, local interpretations have reconstructed its meaning within the Batak Angkola cultural framework. Thus, Candi Sipamutung serves as a living symbol in the collective memory and a medium for preserving cultural identity and local wisdom.